Risk identification, future value and credit capitalization: Research on the theory and policy of poverty alleviation by Internet finance - Yongjian Li; Chengqing Wang (China Finance and Economic Review, 2017)
Background: Elimination of poverty is an important part to achieve a comprehensive well-off in China, and financial means and tool play an important role in it. Methods: This paper employs credit capitalization model and future-oriented valuation method, uses the data from leading enterprise. Results: There are some problems in current financial poverty alleviation practice, such as the lack of unified organization, high cost, poor sustainability, uncertain effects, etc. The internet finance, based on new information technologies which enable more comprehensive information collection of poverty population can help the poor households to accumulate credit capital and play a greater role in the process of poverty alleviation. Conclusions: Although lack of physical capital, the poor people can still benefit from the financial market to get out of poverty and be better off with the support of credit capital through internet finance.
Keywords: 330; Internet finance; Financial poverty alleviation; Poverty alleviation